Improving Indonesian nurse performance on nursing care documentation: A mixed-methods study of a culturally tailored hybrid roleplay intervention - Mahfud, Mahfud; Hartono, Hartono; Subiyanto, Achmad A.; Anantanyu, Sapja (Narra J, 2025)
Nursing documentation is critical for ensuring quality patient care and effective communication among healthcare professionals. However, in low- and middle-income countries (LMICs), documentation practices often fall short due to resource limitations and cultural barriers. This mixed-methods study evaluated a culturally adapted roleplay-based intervention to improve nursing documentation quality among Indonesian nurses. Guided by Kolb's Experiential Learning Theory, this intervention focused on experiential, reflective, and technology-enhanced components to enhance nursing documentation practices. Using a quasi-experimental design, 132 nurses from three public hospitals in Jakarta were assigned to either the treatment or control group. The intervention integrated conventional roleplay, digital simulation, and reflective practice. Quantitative data were collected at baseline, post-intervention, and at a 12-week follow-up, measuring documentation quality, self-efficacy, and cognitive load. Additionally, qualitative data were gathered through semi-structured interviews with 15 experimental group participants. Results showed significant improvements in documentation quality (Cohen’s d=1.28 at T1; d=1.14 at T2), self-efficacy (d=0.99 at T1; d=0.85 at T2), and reductions in cognitive load (d=-0.84 at T1; d=-0.72 at T2), indicating significant and sustained improvements at the 12-week follow-up. Qualitative findings highlighted increased confidence, realism of the scenarios, integration of digital skills, and cultural considerations in documentation practices. Participants' hierarchical structure orientation moderated the effectiveness of the intervention. In conclusion, this study provides evidence that hybrid roleplay interventions can enhance nursing documentation practices in low- and middle-income countries, with a focus on culturally tailored healthcare education.